Evaluation of C1q Status and Titer of De Novo Donor‐Specific Antibodies as Predictors of Allograft Survival. Issue 3 (3rd October 2016) - Wiebe, C.; Gareau, A. J.; Pochinco, D.; Gibson, I. W.; Ho, J.; Birk, P. E.; Blydt‐Hansen, T.; Karpinski, M.; Goldberg, A.; Storsley, L.; Rush, D. N.; Nickerson, P. W.
Abstract : De novo donor‐specific antibodies ( dn DSAs) that develop after renal transplantation are independent predictors of allograft loss. However, it is unknown if dn DSA C1q status or titer at the time of first detection can independently predict allograft loss. In a consecutive cohort of 508 renal transplant recipients, 70 developed dn DSAs. Histologic and clinical outcomes were correlated with the C1q assay or dn DSA titer. C1q positivity correlated with dn DSA titer (p < 0.01) and mean fluorescence intensity (p < 0.01) and was more common in class II versus class I dn DSAs (p < 0.01). C1q status correlated with tubulitis (p = 0.02) and C4d status (p = 0.03) in biopsies at the time of dn DSA development, but not T cell–mediated rejection (TCMR) or antibody‐mediated rejection (ABMR). De novo DSA titer correlated with Banff g, i, t, ptc, C4d scores, TCMR (p < 0.01) and ABMR (p < 0.01). Post‐ dn DSA graft loss was observed more frequently in recipients with C1q‐positve dnDSA (p < 0.01) or dn DSA titer ≥ 1:1024 (p ≤ 0.01). However, after adjustment for clinical phenotype and nonadherence in multivariate models, neither C1q status nor dn DSA titer were independently associated with allograft loss, questioning the utility of these assays at the time of dn DSA development. Abstract : De novo donor‐specific antibody titer and C1q are not independent predictors of allograft survival following de novo donor‐specific antibody development after adjustment for nonadherence and clinical phenotype.